Sequencing of 231 forensic genetic markers using the MiSeq FGx™ forensic genomics system - an evaluation of the assay and software - Christian Hussing; Christina Huber; Rajmonda Bytyci; Helle S. Mogensen; Niels Morling; Claus Børsting (Oxford University Press, 2018)
The MiSeq FGx™ Forensic Genomics System types 231 genetic markers in one multiplex polymerase chain reaction (PCR) assay. The markers include core forensic short tandem repeats (STRs) as well as identity, ancestry and phenotype informative short nucleotide polymorphisms (SNPs). In this work, the MiSeq FGx™ Forensic Genomics System was evaluated by analysing reproducibility, sensitivity, mixture identification and forensic phenotyping capabilities of the assay. Furthermore, the genotype calling of the ForenSeq™ Universal Analysis Software was verified by analysing fastq.gz files from the MiSeq FGx™ platform using the softwares STRinNGS and GATK. Overall, the performance of the MiSeq FGx™ Forensic Genomics System was high. However, locus and allele drop-outs were relatively frequent at six loci (two STRs and four human identification SNPs) due to low read depth or skewed heterozygote balances, and the stutter ratios were larger than those observed with conventional STR genotyping methods. The risk of locus and allele drop-outs increased dramatically when the amount of DNA in the first PCR was lower than 250 pg. Two-person 50:1 mixtures were identified as mixtures, whereas 100:1 and 1 000:1 mixtures were not. Y-chromosomal short tandem repeats (Y-STRs) alleles were detected in the 100:1 and 1 000:1 female/male mixtures. The ForenSeq™ Universal Analysis Software provided the data analyst with useful alerts that simplified the analysis of the large number of markers. Many of the alerts were due to user-defined, locus-specific criteria. The results shown here indicated that the default settings should be altered for some loci. Also, recommended changes to the assay and software are discussed.